THE RELATIONSHIP BETWEEN DIETARY PATTERNS AND THE INCIDENCE OF DYSPEPSIA IN PAYA BENGKUANG VILLAGE: DIETARY PATTERNS - Nasution, Amalia Rahmi; Delfriana Ayu Astuty; Fadila, Nurly; Alayda, Nurul Fifi; Br.Ginting, Alvi Nur Ilmi; Putri, Ghizka Aulia (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Indonesia is a developing country that still faces two major challenges in health development: unresolved issues of communicable diseases and a high incidence of non-communicable diseases, which continue to be problematic. Dyspepsia is one of the most common non-communicable diseases worldwide. In July 2024, data showed 134 cases of dyspepsia in the Gebang sub-district. This research aims to determine the relationship between dietary patterns and the incidence of dyspepsia in Paya Bengkuang Village, Gebang District, Langkat Regency. Methods: The study was conducted using a quantitative descriptive method with a population of 4,661 people and a sample of 100 people. The sampling technique employed was stratified random sampling. Data collection was conducted using questionnaires distributed to each sample Results: The statistical test results indicated a p-value of 0.001 (p-value <0.05) between dietary patterns and the incidence of dyspepsia. Conclusion: The study concludes that there is a significant relationship between dietary patterns and the incidence of dyspepsia in Paya Bengkuang Village.